Project Management in Real Time: A Service-Learning Project - Larson,Erik; Drexler,John (Journal of Management Education, 2010)
This article describes a service-learning assignment for a project management course. It is designed to facilitate hands-on student learning of both the technical and the interpersonal aspects of project management, and it involves student engagement with real customers and real stakeholders in the creation of real events with real outcomes. As such, it helps students internalize project management principles and value project management tools. Student teams design and implement plans for events intended to result in significant contributions in support of various charitable organizations. They create the planning and execution documents required of project management teams. The article describes the assignment and its results and discusses some cautions and alternatives.
Keywords: Management

Business Education and Its Relationship to Student Personal Moral Philosophies and Attitudes Toward Profits: An Empirical Response to Critics - Neubaum,Donald; Pagell,Mark; Drexler,John; Ryan,Fran McKee; Larson,Erik (Academy of Management Learning and Education, 2009)
Critics of business education (e.g., Ghoshal, 2005; Mitroff, 2004) place much of the blame for recent ethical scandals on the lack of moral development of managers and the amoral, "profits-first" theoretical underpinnings of business education. To empirically test these claims, we surveyed 1,080 business and nonbusiness students from a major research university. The results suggest that neither the personal moral philosophies of business and nonbusiness students, nor the personal moral philosophies of business freshmen and business seniors differed significantly. Based on our results, we found no evidence to support the claims of critics who suggest business education is associated with negative personal moral philosophies of students. Further, the attitudes of business freshmen and business seniors concerning profit and sustainability differed significantly, yet in the direction opposite the one Ghoshal (2005) and others would have predicted. Thus, blaming the rash of ethical scandals on the amoral and "profits-first" theoretical underpinnings of business school training might be too simplistic of an approach.
Keywords: Management; Strategy & Entrepreneurship

Fund Raisers as vehicles for teaching project management principles and tools - Drexler,John; Larson,Erik (Journal of Management Education, 2009)
Keywords: Management

Green companies set an example - Wu,Zhaohui; Drexler,John (2007)
Keywords: Management; Supply Chain

Business education, personal moral philosophies and “profits-first” mentalities: An empirical response to critics - Neubaum,Donald; Drexler,John; Larson,Erik; Pagell,Mark; McKee-Ryan,Fran (Academy of Management Annual Meeting, 2006)
Keywords: Management; Strategy & Entrepreneurship

Journal of Management Education Reviewing and Publishing - Drexler,John; Jackson,J. J.; Dean,K. L.; Gillespie,J.; Konz,G. N. (Annual Meeting of the Academy of Management, 2004)
Keywords: Management

Peer appraisals: Differentiation of individual performance on group tasks - Drexler,John; Beehr,T. A.; Stetz,T. A. (Human Resource Management (US), 2001)
The use of peer appraisals has been widely acclaimed, but how useful are they really? Student groups made non-anonymous ratings of peer performance on two group tasks, and the ratings contributed to the students' course grades. Groups differentiated very little among peers in their performance ratings. Individuals in non-differentiating groups reported more positive distributive and procedural justice, satisfaction, and turnover intent than did individuals in differentiating groups. In differentiating groups, no differences in attitudes were found between individuals who were differentially rewarded or penalized for their performance. Implications for peer appraisal practice and future research are discussed. © 2001 John Wiley & Sons, Inc.
Keywords: Management

Partnering: Why Project Owner-Contractor Relationships Change - Drexler,John; Larson,Erik (Journal of Construction Engineering and Management, 2000)
Over the last decade, research in the construction industry has explored the owner-contractor relationship in project management resulting in a different paradigm called partnering. Partnering is a relationship characterized by cooperation and collaboration in contrast to the adversarial relationship more commonly experienced between owners and contractors. This study utilized data collected from 276 construction projects to examine the stability in the owner-contractor relationship. Owner-contractor relationships were classified as being adversarial, guarded adversarial, informal partners, or project partners. Fifty-eight percent of the projects experienced some fundamental change in working relationshipeither positive or negative. Projects that began as formal partnerships were the most stable with over two thirds ending as they began. Guarded adversarial was the least stable with fewer than 30% maintaining this kind of relationship at the end of the project. Content analysis of the reasons stated for the change revealed factors that contribute to an improvement or deterioration in working relationships. The writers use this analysis to make recommendations for sustaining and improving partnerships between owner and contractors.
Keywords: Management

Using total quality processes and learning outcome assessments to develop management curricula - Drexler,John; Kleinsorge,Ilene (Journal of Management Education, 2000)
A process was designed to identify what total quality skills should be included in the authors curriculum and howto deliver them. Customer data led the authors to change their focus toward exploring and assessing what they do in the entire curriculum. The emphasis on learning outcomes is a theme in American Assembly of Collegiate Schools of Business and education reform. The authors summarize things learned that may help others avoid certain pitfalls and build on the authors progress to date.
Keywords: Accounting; Management

Website creation: Integrating information technology skills into the international management curriculum - Drexler,John; Larson,Erik (Annual Meeting of the Academy of Management, 2000)
Keywords: Management

Using a Computer-Based Version of the Beer Game - Larson,Erik; Coakley,James; Drexler,John (Journal of Management Education, 1998)
Keywords: BIS; Management